A hierarchical supply chain model for the sugar–alcohol energy sector with robust optimization analysis. (28th November 2020) - Paiva, Rafael P.; Rocco, Cleber D.; Morabito, Reinaldo
Abstract: This paper addresses a hierarchical optimization model for the sugar–alcohol energy sector with robust optimization analysis to provide managerial insights. It has two levels: the upper level is a linear model in which more aggregated decisions are related to allocating production targets to mills belonging to a cooperative society aiming to meet the potential market demand, as well as managing the inventories over months in annual planning; the lower level is a mixed‐integer model that represents the less aggregated decisions of each mill, such as the milling rhythm, the industrial process selection to produce sugar–alcohol–molasses and energy, purchasing sugarcane from the suppliers on a weekly basis. Robust optimization analysis is performed for product prices and industrial yields to investigate their impacts on the supply chain that could not be inferred through deterministic approaches. One important result was related to the uncertainty in product prices that had a greater impact on the whole supply chain compared to the industrial yield, which affects only the mill itself, particularly increasing the inventory backlog of the mill for not meeting the demand assigned by the cooperative. Cogeneration of energy, and the sale of surplus energy was an important strategy to mitigate the decrease in industrial yield performed in the robust analysis while the change in the product production pattern was a consequence of product price uncertainty. The models can be applied in practice to provide better strategic and tactical planning of mills in cooperatives.